Behavior of the Leached Metal Ions in Copper Cementation - Lovera, Daniel (2009)
This article describes the cementation process of leached solutions from copper sulphide ores being and without being toasted. With favorable results in this study, we get the pattern for the feasibility of moving from the classical technology of concentration to the technology of cementation of copper sulfide minerals containing silver and gold. Simulation steps have been performed considering the different variables involved in the process such as time, agitation, solution concentration, pH and others. A kinetic model of copper cementation from PLS solutions purified by Solvent Extraction (SX) has been developed and it has the following form: C = 6.08 exp (- 0.03 t) Recoveries were obtained greater than 90% copper, which gives the possibility to improve the costs of national ores and con- centrates, as well as to open a favorable scenario for new national metallurgical projects.